Effectiveness of Practicum Activities as an Effort to Improve Student Learning Outcomes at SMA Negeri 2 Tondano - Yestika Lolowang; Arrijani Arrijani; Nova L. I. M. Ogi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to determine the effectiveness of practicum activities to improve student learning outcomes at SMA Negeri 2 Tondano. This type of research is quantitative descriptive research that uses a survey method to describe and explain data based on the reality in the field. The research was carried out by distributing questionnaires to teachers and students, observation sheets, and practical activity sheets with data sources consisting of 30 students of class X Science 1, 30 students of class X Science 2, and biology teachers. Based on the research results, the level of readiness to obtain data for class X IPA 1 At the implementation stage of the practicum activities for class X Science 1 is 91%; the efforts made to improve the quality of practicum implementation are by improving practicum weaknesses such as the availability of tools and materials, good laboratory management, conducting evaluations, arranging implementation schedules and paying attention to laboratory layout in order to carry out practicum optimally. The factors that influence the quality of practicum implementation include student motivation, limited tools and materials, practicum schedule, availability of facilities and infrastructure, teacher's role in practicum activities, and students' active thinking.